Reduction in new cardiac electronic device implantations in Catalonia during COVID-19. Issue 3 (17th February 2021) - Arbelo, Elena; Angera, Ignasi; Trucco, Emilce; Rivas-Gándara, Nuria; Guerra, José M; Bisbal, Felipe; Jáuregui-Abularach, Miguel; Vallés, Ermengol; Martin, Gabriel; Sbraga, Fabrizio; Tolosana, José María; Linhart, Markus; et al.
Abstract: Aims: During the COVID-19 pandemic, concern regarding its effect on the management of non-communicable diseases has been raised. However, there are no data on the impact on cardiac implantable electronic devices (CIED) implantation rates. We aimed to determine the impact of SARS-CoV2 on the monthly incidence rates and type of pacemaker (PM) and implantable cardiac defibrillator (ICD) implantations in Catalonia before and after the declaration of the state of alarm in Spain on 14 March 2020. Methods and results: Data on new CIED implantations for 2017–20 were prospectively collected by nine hospitals in Catalonia. A mixed model with random intercepts corrected for time was used to estimate the change in monthly CIED implantations. Compared to the pre-COVID-19 period, an absolute decrease of 56.5% was observed (54.7% in PM and 63.7% in ICD) in CIED implantation rates. Total CIED implantations for 2017–19 and January and February 2020 was 250/month (>195 PM and >55 ICD), decreasing to 207 (161 PM and 46 ICD) in March and 131 (108 PM and 23 ICD) in April 2020. In April 2020, there was a significant fall of 185.25 CIED implantations compared to 2018 [95% confidence interval (CI) 129.6–240.9; P < 0.001] and of 188 CIED compared to 2019 (95% CI 132.3–243.7; P < 0.001). No significant differences in the type of PM or ICD were observed, nor in the indication for primary or secondary prevention. Conclusions: During the first wave of the COVID-19 pandemic, a substantial decrease in CIED implantations was observed in Catalonia. Our findings call for measures to avoid long-term social impact.